Prevalence and Clinical Burden of NDM-1 Positive Infections in Pediatric and Neonatal Patients in Pakistan. Issue 4 (April 2015) - Qamar, Muhammad Usman; Nahid, Fouzia; Walsh, Timothy R.; Kamran, Rubina; Zahra, Rabaab
<x xml:space="preserve">Abstract</x> In a neonatal/pediatric Gram-negative infection study from Islamabad, 71/82 strains were carbapenem resistant with 12/82 positive for New Delhi Metallo-β-lactamase and many being extensively antibiotic resistant. Burden and outcome analysis on 9 patients showed that 4/9 died after inadequate therapy regardless of organism type.